C57BL/6 Substrains Exhibit Different Responses to Acute Carbon Tetrachloride Exposure: Implications for Work Involving Transgenic Mice - McCracken, Jennifer M. (Gene Expr, 2017)
Biological differences exist between strains of laboratory mice, and it is becoming increasingly evident that there are differences between substrains. In the C57BL/6 mouse, the primary substrains are called 6J and 6N. Previous studies have demonstrated that 6J and 6N mice differ in response to many experimental models of human disease. The aim of our study was to determine if differences exist between 6J and 6N mice in terms of their response to acute carbon tetrachloride (CCl(4)) exposure. Mice were given CCl(4) once and were euthanized 12 to 96 h later. Relative to 6J mice, we found that 6N mice had increased liver injury but more rapid repair. This was because of the increased speed with which necrotic hepatocytes were removed in 6N mice and was directly related to increased recruitment of macrophages to the liver. In parallel, enhanced liver regeneration was observed in 6N relative to 6J mice. Hepatic stellate cell activation occurred earlier in 6N mice, but there was no difference in matrix metabolism between substrains. Taken together, these data demonstrate specific and significant differences in how the C57BL/6 substrains respond to acute CCl(4), which has important implications for all mouse studies utilizing this model.